Trophoblastic Disease: Review of the Literature - Launikonytė, Gabrielė; Korsakaitė, Klaudija; Bužinskienė, Diana (Lietuvos chirurgija, 2022)
The purpose of this literature review is to discuss the most effective gestational trophoblastic disease diagnostic and treatment methods. Also, to introduce some of the novel treatment options currently being explored. A comprehensive research was carried out on scientific databases of MEDLINE and PubMed over the time period of 2014 to 2021. According to literature sources initial gestational trophoblastic disease diagnosis is multimodal: encompassing clinical features, quantitative human chorionic gonadotropin titers and pelvic ultrasonography. Pelvic magnetic resonance imaging, body computed tomography, chest radiography and angiography are the methods usually used for overall disease staging and metastases detection. The best treatment method is designated with reference to individual features of the patient and the disease. Conventional treatment consists of hysterectomy and chemotherapy; however, the use of new methods, such as directed enzyme prodrug therapy is also being attempted to cure metastasized and/or resistant gestational trophoblastic neoplasias. Most women with gestational trophoblastic disease can be successfully managed with preservation of reproductive function due to early diagnosis in the first trimester of pregnancy. It is important to identify gestational trophoblastic disease promptly and adjust specific treatment for every patient properly to minimize various complications.
Keywords: gestational trophoblastic disease; gestational trophoblastic neoplasia; choriocarcinoma; human chorionic gonadotropin